The Image of Jewry in the Works of Art Spiegelman and Saul Bellow - Uherová, Alena (Univerzita Pardubice, 2008)
The aim of this thesis is to find the image of Jewish identity in the works of Saul Bellow and Art Spiegelman. The first part is dealing with introduction to the context of Jewish-American history, literature and identity. The main body of the thesis explores the way of reflection on Jewish-American identity in the works Maus and Mr Sammler’s Planet. Based on the literary connections of the works examined, the attention is focused on the analysis and comparison of these novels. Special attention is paid to the image of faith, Jewish stereotypes, racial prejudices, family relationships, settling down the past, identity crisis and Jewish continuity. Also the formal aspects and uniqueness of these works are mentioned. The conclusion deals with assessment of the Jewry image based on the analysis and comparison of the works.
Vyobrazení židovství v pracích Arta Spiegelmana a Saula Bellowa
Keywords: Americká židovská literatura; Židé; židovská identita; jewish-american literature; Saul Bellow; Art Spiegelman; Mr Sammler's planet; Jews; Jewish identity